[Akureyri Along Eyjafjordur] - Streng, Evelyn Fiedler (1975)
Photograph of Akureyri, Iceland along Eyjafjordur. The city is sat against the water, its buildings stood in lines throughout in a tight cluster. Green hills and mountains cover the background, white clouds obscuring the top of the mountain. A hill covered in grass and dirt sit at the bottom of the photograph.